Animal modeling an oligodendrogliopathy – multiple system atrophy - Bleasel, Jonathan M. (Acta Neuropathol Commun, 2016)
Multiple system atrophy (MSA) is a rare, yet rapidly-progressive neurodegenerative disease that presents clinically with autonomic failure in combination with parkinsonism or cerebellar ataxia. The definitive neuropathology differentiating MSA from Lewy body diseases is the presence of α-synuclein aggregates in oligodendrocytes (called glial cytoplasmic inclusion or GCI) rather than the fibrillar aggregates in neurons (called Lewy bodies). This makes the pathological pathway(s) in MSA unique in that oligodendrocytes are involved rather than predominantly neurons, as is most other neurodegenerative disorders. MSA is therefore regarded as an oligodendrogliopathy. The etiology of MSA is unknown. No definitive risk factors have been identified, although α-synuclein and other genes have been variably linked to MSA risk. Utilization of postmortem brain tissues has greatly advanced our understanding of GCI pathology and the subsequent neurodegeneration. However, extrapolating the early pathogenesis of MSA from such resource has been difficult and limiting. In recent years, cell and animal models developed for MSA have been instrumental in delineating unique MSA pathological pathways, as well as aiding in clinical phenotyping. The purpose of this review is to bring together and discuss various animal models that have been developed for MSA and how they have advanced our understanding of MSA pathogenesis, particularly the dynamics of α-synuclein aggregation. This review will also discuss how animal models have been used to explore potential therapeutic avenues for MSA, and future directions of MSA modeling.